Impulsivity, drug use, type of crime and risk of suicide in young Mexican imprisoned men - Santana-Campas, Marco Antonio; Hidalgo-Rasmussen, Carlos Alejandro; Santoyo Telles, Felipe (Acta Universitaria, 2019)
The suicidal risk is higher in imprisoned young people than in the open population. The objective of this study was to identify the effect of impulsivity, drug use, and type of crime on the risk of suicide in young imprisoned men.  A cross-sectional study was conducted through a convenience sample retrieved from four out of 13 prisons in the state of Jalisco, Mexico. Plutchik’s impulsivity and suicide risk scales were applied to identify drugs use, type of crime, and sociodemographic variables. The subjects were 331 men between 15 to 29 years old, with an average age of 23.78 (SD = 4.26). The results show that impulsiveness increases the possibility of suicidal risk among young imprisoned men by 5.6 (2.9-10.6) times more and drugs consumption 3.7 (1.2-11.2) times more.